Incorporating knowledge of allelopathic interactions can improve productivity and sustainability of crop rotations in the semi-arid tropics - Nageswara Rao Vajja; Holger Meinke; Martin J. Kropff; Niels P. Anten; Anthony M. Whitbread; Uttam Kumar; David Parsons (Journal of Agriculture and Food Research)
Allelopathy in rainfed crop production systems can be a boon or bane for smallholder farmers depending on their crop choices in intercrops, sequences, and rotations. Crop and weed allelopathy can lead to serious problems like poor germination, low crop stand, and reduced crop growth and productivity. Residual toxicity in soil due to allelopathic monocultures and detrimental impacts on ecosystems, human habitats and health are other problems caused by allelopathy. Allelopathy can be exploited to control weeds, reduce herbicide use, avoid herbicide resistance, stimulate crop growth, and enhance nutrient availability.This review aims to provide practical knowledge that can improve the management of farming systems in the semi-arid tropics of the Indian subcontinent, a region prone to allelopathic effects induced by biotic and abiotic stresses. We focus on synergistic and antagonistic allelopathic effects of major cereals, legumes, oilseeds, commercial crops, and weeds and summarise the current knowledge on the mode of release and properties of allelochemicals in crops, residue management and their impacts on crops and weeds. We then list options to effectively suppress weeds, reduce risks of residual toxicity in soil and environmental hazards and outline synergistic crop rotations that reduce disease build up and eradicate parasitic weeds in rainfed production systems of the semi-arid tropics. Finally, we highlight research gaps to further improve and employ knowledge of allelopathy of weeds and crops for improved crop production, with reduced synthetic herbicide usage.